2013
DOI: 10.2340/00015555-1531
|View full text |Cite
|
Sign up to set email alerts
|

Skin pH: From Basic SciencE to Basic Skin Care

Abstract: The "acid mantle" is a topic not only of historical interest, but also of clinical significance and has recently been linked to vital stratum corneum function. Despite compelling basic science evidence placing skin pH as a key factor in barrier homeostasis, stratum corneum integrity, and antimicrobial defense, application of the acid mantle concept in clinical care is lacking. We review recent basic science investigations into skin pH, discuss skin disorders characterized by aberrant pH, and finally discuss pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
413
1
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(446 citation statements)
references
References 73 publications
10
413
1
22
Order By: Relevance
“…Most reports have suggested that a pH between 4 and 6.5 can be considered as adequate for cosmetic formulations since most pathogenic bacteria (e.g. S. aureus), thrive best at neutral pH levels (Ali and Yosipovitch, 2013). In the present work, the cosmeceutical formulation presented a pH 4.6, which is considered within the favourable pH range.…”
Section: G Lucidum Ethanolic Extracts In Cosmeceutical Formulationsmentioning
confidence: 63%
See 1 more Smart Citation
“…Most reports have suggested that a pH between 4 and 6.5 can be considered as adequate for cosmetic formulations since most pathogenic bacteria (e.g. S. aureus), thrive best at neutral pH levels (Ali and Yosipovitch, 2013). In the present work, the cosmeceutical formulation presented a pH 4.6, which is considered within the favourable pH range.…”
Section: G Lucidum Ethanolic Extracts In Cosmeceutical Formulationsmentioning
confidence: 63%
“…The rate of dermal absorption of topical formulations such as lotions and creams are often influenced by the pH of the product. The pH of skin external surface is around 5.5, and at this condition, the skin micro-flora, barrier homeostasis and stratum corneum are maintained (Ali and Yosipovitch, 2013;Martínez-Pla et al, 2004). Most reports have suggested that a pH between 4 and 6.5 can be considered as adequate for cosmetic formulations since most pathogenic bacteria (e.g.…”
Section: G Lucidum Ethanolic Extracts In Cosmeceutical Formulationsmentioning
confidence: 99%
“…A cosmetic is any substance or preparation intended for external contact with the human body: skin, hair, lips, nails, external genital organs, teeth and mucous membranes oral, and its sole or primary purpose is to maintain cleanliness of these body parts, to improve appearance of the body or improve its smell [4].…”
mentioning
confidence: 99%
“…-активность ферментов β-глюкоцереброзидазы и кислой сфингомиелиназы -ключевых ферментов, участвующих в регуляции проницаемости кожи [10];…”
Section: клиническая дерматология и венерология 2 2016unclassified
“…Это является причиной выраженно-го градиента рН (2-3 ед.) между рН рогового слоя и рН эпидермиса и дермы [10]. Повышение уровня рН способствует росту активности сериновой протеа-зы, калликреина 5 и 7, которые участвуют в десква-мации и деградации корнеодесмосом [17].…”
Section: природные буферные системы кожиunclassified